Pemahaman Mahasiswa Terhadap Integral sebagai Anti Turunan, Suatu Desain Riset pada Kalkulus Integral - Tasman, Fridgo; Ahmad, Defri (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2017)
The low learning outcomes and studentâs difficulties in understanding calculus courses, espe-cially integral topic, encourage us as researcher to design a calculus lesson for first year students by using realistic mathematical approach (Realistic Mathematics Education). For that we try to design a series of instructional activities starting from understanding integral as an anti derivative. The in-structional activity is designed and developed based on the learning process that occurs in the class-room by involving 30 first year students in FMIPA UNP. The classroom learning compared with our Hypothetical Learning Trajectory (HLT). The results of teaching experiment show that students un-derstanding of derivative plays important role in understanding the integrals, in general students have difficulty in communicating their ideas in determining the anti-derivative of a function. Through class-room discussions students can get ideas and discuss it in determining the anti-derivative of a function. Based on these results it is recommended to conduct classroom discussions to build students under-standing in studying calculus especially integral as an anti derived.